MARKETING VALUE: REDEFINISI FUNGSI DAN MAKNA BRAND - Moh. Muzwir Luntajo (Jurnal Ilmiah Al-Syir'ah, 2006)
Brand in this time in global economic environment non again just a name. At marketing company, brand do not simply soul have to all product, but more than that. When branding have become the spirit company, hence each every product will be saleable by it self. That's one of the 'core' a marketing company in improving its customer base